THE PROMISING ACTIVITY OF ZINGIBER OFFICINALE (GINGER) AGAINST COVID-19: A LITERATURE REVIEW - da Silva Pamplona, Lucas; Cristina Silva, Natasha (Health and Society, 2023)
On the premise that scientific evidence pointing to the pharmacological properties of Zingiber officinale, the present work, through a literature review carried out in the main databases, such as Periódico da Capes, PubMed, ScienceDirect, Scielo and Cochrane, investigates the activities biological agents that correlate ginger with antiviral action against SARS-CoV-2, the etiological agent of COVID-19. Undoubtedly, the plant has shown to have a range of bioactive compounds with the proposed action, through molecular docking tests which were found to be in the essential oil of the rhizome. These assays demonstrated the metabolite’s ability to bind to several viral components belonging to SARS-CoV-2, such as proteases, Spike protein, RNA binding protein and N-terminal RNA-binding domain, emphasizing an antiviral action. On the other hand, even though science agrees that in Zingiber officinale extracts, there is a possibility of an answer to cure many ailments, which include the promising anti-COVID-19 activity, there is still a lack of in-depth studies on their metabolites, which can serve as an active pharmaceutical ingredient of a new pharmaceutical formulation amid the search for new drugs in the current scenario governed by the pandemic.